Dangerous pesticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The use of pesticides chemically related to DDT to eradicate tsetse flies has proved to be dangerous to human health. In Zimbabwe, studies show human milk to be twice as contaminated with DDT as any sample previously tested by the World Health...